Nano-chip for cancer diagnostics - Manaj, L.; Manaj, L.; Joubert, I.A.; Geppert, M.; Himly, M. (Open Schools Journal for Open Science, 2020)
Exosomes are vesicles with a size range of 30 to 50 nm, which are secreted by a cell into its surroundings. They are currently investigated as possible biomarkers for teh detection of early stage cancer, infections or autoimmune siseases. To identify which exosomes could contain viable markers, they have been isolated form body fluids such as blood, urine, or salive and have subsequently undergone screening procedures Exosome isolation has, so far, been performed by ultra-centrifugation, a time-consuming prcedure that requaires large volumes of the fluid sample.